Analysis of the Bengkalis Regency Government's 'Bermasa' Special Financial Aid (BKK) Policy to Improve the Quality and Efficiency of Government Services - Pratama, Adrian Irnanda; Bustami, Bustami; Rosa, Nageeta Tara (Politeknik Negeri Bengkalis, 2024)
This study aims to analyze the BKK